Spatial development of regensburg/ratyzbona towards the city of "green" housing estates - Wojtyszyn, Bogusław J. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article raises important issues related to global threats to the urban environment and methods of its protection on a scale from urban planning to architectural design. The research undertaken in this respect was conducted on the selected medium-sized German city of Regensburg/Ratyzbona. This is a city that has for many years been implementing a spatial development policy in line with the principles of sustainable development.
Keywords: sustainable city development; sustainable urban development; urban development; zrównoważony rozwój miasta; rozwój zrównoważony; rozwój obszarów miejskich